Bayesian estimation of the Cox model under different hazard rate shape assumptions via slice sampling. Issue 12 (10th September 2018) - Kirschenmann, Thomas; Damien, Paul; Walker, Stephen
ABSTRACT: In this paper, we provide a full Bayesian analysis for Cox's proportional hazards model under different hazard rate shape assumptions. To this end, we select the modified Weibull distribution family to model failure rates. A novel Markov chain Monte Carlo method allows one to tackle both exact and right-censored failure time data. Both simulated and real data are used to illustrate the methods.